Elucidating the genomic architecture of Asian EGFR-mutant lung adenocarcinoma through multi-region exome sequencing - Rahul Nahar (Nature Portfolio, 2018)
EGFR mutant lung adenocarcinoma (LUAD) exhibit diverse clinical outcomes in response to targeted therapies. Here the authors show that these LUADs involve a complex genomic landscape with high intratumor heterogeneity, providing insights into the evolutionary trajectory of oncogene-driven LUAD and potential mediators of EGFR TKI resistance.